The Determinant Factors of Purchase Intention in the Culinary Business in Indonesia That Mediated by Parasocial Interaction and Food Vlogger Credibility - et. al., Lilian Pinda (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze the relationship between physical attractiveness, attitude homophily, social attractiveness, openness, interactivity, credibility, parasocial interaction, and purchase intention on YouTube in the culinary business in Indonesia. This research is a causal research design that applies the Structural Equation Modeling (SEM) research model as a method of data analysis. Using convenience sampling, the study sample involved 202 respondents as YouTube users in Jakarta and its surroundings who watched food review content by food vloggers more than three times a month. Based on the results of the hypothesis test, the factors that influence social interaction are physical attractiveness, social attractiveness, and interactivity. Meanwhile, only physical attractiveness affects food vlogger credibility. Therefore, before deciding to collaborate with a food vlogger, marketers can understand how credibility is formed and the interaction between a food vlogger and its audience on social media so that it can influence the audience's buying interest